2011
DOI: 10.1007/s00894-011-1283-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of the phenylhalocarbenes. Are they spin-allowed or spin-forbidden reactions?

Abstract: Oxygenation mechanisms of phenylhalocarbenes in vacuum are investigated through the use of density functional theory and CASSCF-PT2 approaches. Reactions with both substituted and unsubstituted phenylhalocarbenes are strongly exothermic. The reactions with nitrosubstituted halocarbenes are predicted to be spin allowed due to the practical degeneracy of the singlet and triplet carbene states. Conversely, for the unsubstituted compounds, the equilibrium between the triplet carbene and (3)O(2) requires a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Time-dependent DFT (TDDFT) methods were employed to calculate the vertical excitation energies of 2a – 5a and 2b – 5b to estimate whether the compounds were photodynamically active. According to literature procedures, the use of TDDFT with the B3LYP functional and the 6-31G* basis set provides a useful estimate of the energy difference between the singlet ground-state (S 0 ) and the vertical triplet excited state. ,, We optimized the geometry using symmetry-unrestricted DFT methods at B3LYP/6-31G* and then performed single-point energy calculations using TDDFT methods at the same level of theory to determine the vertical excitation energies of 2a – 5a and 2b – 5b . The calculations were performed in the gas phase because it has been shown that for excitation calculations at this level the effects of the solvent are negligible. , These calculations were used to investigate the potential of these bacteriochlorins to generate type 2 PDT ROS. Type 2 PDT require the vertical singlet–triplet excitation energy gap (Δ E ST ) of PSs to be greater than 0.98 eV to transfer energy from their triplet excited state to ground-state molecular oxygen ( 3 O 2 ) to produce singlet oxygen ( 1 O 2 ). These Δ E ST calculations showed that 2a – 5a and 2b – 5b were each capable of undergoing type 2 PDT (Table S3) and that the Δ E ST values of the compounds without the exocyclic E ring ( 2b – 5b : Δ E ST = 1.5445–1.6218 eV) are consistently higher than that of compounds with the exocyclic E ring ( 2a – 5a ; Δ E ST = 1.4926–1.5172 eV) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-dependent DFT (TDDFT) methods were employed to calculate the vertical excitation energies of 2a – 5a and 2b – 5b to estimate whether the compounds were photodynamically active. According to literature procedures, the use of TDDFT with the B3LYP functional and the 6-31G* basis set provides a useful estimate of the energy difference between the singlet ground-state (S 0 ) and the vertical triplet excited state. ,, We optimized the geometry using symmetry-unrestricted DFT methods at B3LYP/6-31G* and then performed single-point energy calculations using TDDFT methods at the same level of theory to determine the vertical excitation energies of 2a – 5a and 2b – 5b . The calculations were performed in the gas phase because it has been shown that for excitation calculations at this level the effects of the solvent are negligible. , These calculations were used to investigate the potential of these bacteriochlorins to generate type 2 PDT ROS. Type 2 PDT require the vertical singlet–triplet excitation energy gap (Δ E ST ) of PSs to be greater than 0.98 eV to transfer energy from their triplet excited state to ground-state molecular oxygen ( 3 O 2 ) to produce singlet oxygen ( 1 O 2 ). These Δ E ST calculations showed that 2a – 5a and 2b – 5b were each capable of undergoing type 2 PDT (Table S3) and that the Δ E ST values of the compounds without the exocyclic E ring ( 2b – 5b : Δ E ST = 1.5445–1.6218 eV) are consistently higher than that of compounds with the exocyclic E ring ( 2a – 5a ; Δ E ST = 1.4926–1.5172 eV) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Following this, symmetry-unrestricted, gas-phase TDDFT single-point energy calculations were performed for the triplet excited state using the ground-state-optimized geometry. The vertical excitation energies for the compounds were obtained from this calculation. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation